High-entropy alloy and preparation method thereof
By performing annealing treatment in high-entropy alloys, the gradient distribution of annealing temperature is achieved, and the problem of difficulty in taking into account the hardness and toughness of high-entropy alloys is solved. High-entropy alloys with 'outside hardness and inner toughness' are prepared, which improves their high-temperature resistance Application potential of grinding performance.
Patent Information
- Application Number
- CN202411241755.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
High-entropy alloys have high hardness at high temperatures but have brittleness at the same time, making it difficult to take into account both hardness and toughness, which limits its application in the field of high-temperature wear resistance.
By smelting, casting and forging the alloy raw materials, and then annealing treatment on one side, the gradient distribution of the annealing temperature is achieved, so that the gradient increases the hardness and achieves the characteristic of "hardness on the outside and toughness on the inside".
The surface hardness of the prepared high-entropy alloy reaches HV740 or above, the hardened layer depth is 2 to 4 mm, and the impact toughness of the core is greater than 60J/cm2, achieving hardness gradient distribution and high toughness.
Smart Images

Figure CN119120959A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy alloys, and in particular relates to a high entropy alloy and a preparation method thereof. Background Art
[0002] High entropy alloys have a high-temperature hysteresis diffusion effect. At high temperatures, atoms diffuse slowly and the second phase is not easy to grow. Therefore, it is possible to obtain excellent high-temperature wear resistance. However, high entropy alloys usually have a high brittleness problem while having high hardness, which seriously limits the application of high entropy alloys in the field of high-temperature wear resistance.
[0003] With the help of design ideas in the field of steel materials, can we also achieve "hard outside and tough inside" in high entropy alloys to solve the problem that it is difficult to balance high hardness and brittleness of high entropy alloys? Carburizing or nitriding high entropy alloys, the nitriding layer is shallow, usually only tens of microns, and it is difficult to achieve technical target requirements. It is also not easy to obtain the characteristics of "hard outside and tough inside" in high entropy alloys using rapid cooling processes such as induction quenching.
[0004] Unlike conventional metal materials that have the phenomenon of "annealing softening", high entropy alloys have the phenomenon of "annealing hardening", that is, high temperature annealing will significantly increase the hardness. The mechanism of "annealing hardening" is that a large amount of precipitates will be produced during the annealing process, leading to second phase precipitation strengthening. For FCC-based high entropy alloys, the cast or hot-rolled state has excellent toughness, and the hardness will be significantly improved after high temperature annealing, but at the same time it will become brittle. The reduction in toughness seriously limits the application of high entropy alloys.
[0005] Therefore, how to improve the process so that the hardness of the high entropy alloy is gradiently distributed and has the characteristics of "hard outside and tough inside" has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a high entropy alloy and a preparation method thereof. The high entropy alloy prepared by the preparation method provided by the present invention has a gradient hardness distribution and has the characteristics of "hard outside and tough inside".
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a high entropy alloy, comprising the following steps:
[0009] (1) melting, casting and forging the alloy raw materials in sequence to obtain a wrought alloy;
[0010] (2) Annealing one side of the wrought alloy obtained in step (1) to obtain a high entropy alloy.
[0011] Preferably, the smelting temperature in step (1) is 1500-1600° C., and the smelting time is 0.5-2 h.
[0012] Preferably, the start forging temperature in step (1) is 1150-1200° C., and the forging ratio is 4-5.
[0013] Preferably, the rate of heating to the start forging temperature is 1-3°C / min.
[0014] Preferably, the thickness of the wrought alloy in step (2) is ≥10 mm.
[0015] Preferably, the holding temperature of the annealing treatment in step (2) is 650-700° C., and the holding time of the annealing treatment is 4-10 hours.
[0016] Preferably, the core temperature of the wrought alloy during the annealing treatment in step (2) is below 400°C.
[0017] Preferably, the hardened layer thickness of the high entropy alloy in step (2) is 2 to 4 mm.
[0018] The present invention also provides a high entropy alloy prepared by the preparation method described in the above technical solution.
[0019] Preferably, the composition includes, by atomic ratio, 28-30% iron, 28-30% chromium, 18-20% nickel, 18-20% manganese, 1.8-3.8% vanadium and 1.0-2.2% aluminum.
[0020] The present invention provides a method for preparing a high entropy alloy, comprising the following steps: melting, casting and forging alloy raw materials in sequence to obtain a wrought alloy; annealing one side of the wrought alloy to obtain a high entropy alloy. The present invention anneals one side of the wrought alloy, which can achieve a gradient distribution of annealing temperature in the high entropy alloy, wherein the annealing temperature is high on the side close to the annealing treatment and low on the side away from the annealing treatment, so that the second phase precipitation strengthening effect changes in a gradient, thereby being able to gradually increase the hardness of the high entropy alloy, and obtaining a high entropy alloy with a hardness gradient distribution, wherein the hardness gradually decreases from the surface to the core, and has the characteristics of "hard outside and tough inside". Experimental results show that the surface hardness of the high entropy alloy prepared by the present invention reaches above HV740, the depth of the hardened layer is 2 to 4 mm, and the impact toughness of the core is greater than 60 J / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structure of the gradient annealing furnace used in the embodiment;
[0022] In the figure, 1 is the sample, 2 is the thermocouple, 3 is the insulation cotton, 4 is the cover plate, 5 is the furnace lining, and 6 is the electric heating element;
[0023] Figure 2 is the hardness gradient distribution curve of the high entropy alloy prepared in Example 1;
[0024] Figure 3 This is a surface microstructure diagram of the high entropy alloy prepared in Example 1;
[0025] Figure 4 The core microstructure of the high entropy alloy prepared in Example 1
[0026] Figure 5 The hardness curves of high entropy alloys at different annealing temperatures in the comparative example;
[0027] Figure 6 is the hardness gradient distribution curve of the high entropy alloy prepared in Example 2;
[0028] Figure 7 This is a surface microstructure diagram of the high entropy alloy prepared in Example 2;
[0029] Figure 8 This is a microstructure diagram of the core of the high entropy alloy prepared in Example 2;
[0030] Fig. 9 is the hardness gradient distribution curve of the high entropy alloy prepared in Example 3;
[0031] Fig.10 This is a surface microstructure diagram of the high entropy alloy prepared in Example 3;
[0032] Fig.11 This is the core microstructure diagram of the high entropy alloy prepared in Example 3. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a high entropy alloy, comprising the following steps:
[0034] (1) melting, casting and forging the alloy raw materials in sequence to obtain a wrought alloy;
[0035] (2) Annealing one side of the wrought alloy obtained in step (1) to obtain a high entropy alloy.
[0036] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0037] The invention sequentially smelts, casts and forges the alloy raw materials to obtain a wrought alloy.
[0038] The present invention has no special limitation on the composition of the alloy raw material, and conventional adjustments can be made according to the final composition of the high entropy alloy.
[0039] In the present invention, the smelting temperature is preferably 1500-1600°C, more preferably 1520-1550°C; the smelting time is preferably 0.5-2h, more preferably 1-1.5h. The smelting of the present invention can make the alloy raw materials completely smelted evenly.
[0040] In the present invention, the smelting is preferably carried out under vacuum conditions; the vacuum degree is preferably 1.0×10 -3 ~2.0×10 -3 Pa.
[0041] After smelting is completed, the present invention preferably turns off the power supply, and then allows the molten alloy to stand for a period of 2 to 8 minutes, more preferably 5 minutes. The present invention uses standing to facilitate the floating of inclusions in the molten alloy and improve the purity of the molten alloy.
[0042] The present invention has no special limitation on the casting operation, and operations well known to those skilled in the art may be adopted.
[0043] In the present invention, the forging is preferably hot forging; the start forging temperature of the forging is preferably 1150-1200°C, more preferably 1180°C; the final forging temperature of the forging is preferably 1020-1070°C, more preferably 1050°C; the forging ratio of the forging is preferably 4-5, more preferably 4.90.
[0044] In the present invention, the rate of heating to the start forging temperature is preferably 1-3°C / min, more preferably 3°C / min.
[0045] After forging is completed, the present invention preferably cools the forged product to obtain a wrought alloy.
[0046] In the present invention, the cooling is preferably air cooling.
[0047] After obtaining the wrought alloy, the present invention performs annealing treatment on one side of the wrought alloy to obtain a high entropy alloy.
[0048] In the present invention, the thickness of the wrought alloy is preferably ≥10 mm, more preferably 10 to 40 mm. The present invention limits the thickness of the wrought alloy to the above range, which is beneficial to the subsequent annealing treatment and can avoid the annealing treatment being too thin.
[0049] In the present invention, the wrought alloy is preferably cut before use. The present invention has no special limitation on the cutting operation, and the cutting operation can be adjusted according to the actual required size.
[0050] In the present invention, the holding temperature of the annealing treatment is preferably 650-700°C, more preferably 660-680°C; the holding time of the annealing treatment is preferably 4-10h, more preferably 6-8h; the cooling method of the annealing treatment is preferably air cooling. The present invention has no special limitation on the operation of the air cooling, and the operation familiar to those skilled in the art can be adopted. In the present invention, the holding temperature of the annealing treatment is the surface temperature of the annealing side of the forged alloy; limiting the holding temperature and time of the annealing treatment within the above range can ensure that the surface hardness of the high entropy alloy reaches above HV740.
[0051] In the present invention, the core temperature of the wrought alloy during the annealing treatment is preferably 400° C. or less, more preferably 310-380° C., and even more preferably 350° C. In the present invention, the core is the surface of the side not subjected to the annealing treatment to the hardened layer.
[0052] In the present invention, the rate of heating to the annealing treatment holding temperature is preferably 5 to 15° C. / min, more preferably 8 to 10° C. / min.
[0053] In the present invention, the thickness of the hardened layer of the high entropy alloy is preferably 2-4 mm. In the present invention, the thickness of the hardened layer is the distance from the annealed side surface to the hardness of HV650.
[0054] In the present invention, the annealing treatment is preferably carried out in a gradient annealing furnace. The present invention has no special limitation on the structure of the gradient annealing furnace, and a conventional furnace can be provided with an open lid.
[0055] The present invention performs annealing treatment on one side of the wrought alloy, which can realize a gradient distribution of annealing temperature in the high entropy alloy, wherein the annealing temperature is high on the side close to the annealing treatment and low on the side far from the annealing treatment, so that the effect of second phase precipitation strengthening changes in a gradient, thereby being able to gradually increase the hardness of the high entropy alloy, and obtaining a high entropy alloy with a hardness gradient distribution, wherein the hardness gradually decreases from the surface to the core, and has the characteristics of "hard outside and tough inside".
[0056] The present invention also provides a high entropy alloy prepared by the preparation method described in the above technical solution.
[0057] In the present invention, the composition of the high entropy alloy preferably includes, by atomic ratio, 28-30% iron, 28-30% chromium, 18-20% nickel, 18-20% manganese, 1.8-3.8% vanadium and 1.0-2.2% aluminum, and more preferably 29-30% iron, 29-30% chromium, 19-20% nickel, 19-20% manganese, 2.2-3.8% vanadium and 1.8-2.2% aluminum.
[0058] The high entropy alloy provided by the present invention has a gradient hardness distribution from the surface to the core; the surface hardness reaches above HV740, the core hardness is below HV380; the hardened layer depth is 2 to 4 mm; the impact toughness of the core is a ku More than 60J / cm 2 .
[0059] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] The structural schematic diagram of the gradient annealing furnace used in the embodiment is as follows Figure 1 As shown; in the figure, 1 is the sample, 2 is the thermocouple, 3 is the insulation cotton, 4 is the cover plate, 5 is the furnace lining, and 6 is the electric heating element.
[0061] from Figure 1 It can be seen that the gradient annealing furnace includes a furnace with one end open, a cover plate, a sample window and thermal insulation cotton; the furnace is cylindrical with one end open, the inner diameter of the furnace is 250mm, and the height is 150mm; a cover plate is installed at the open end of the furnace, the diameter of the cover plate is 260mm, the thickness is 10mm, and the material is 304 stainless steel; a sample window is reserved on the cover plate, the shape is square, and the size is 39×39mm; thermal insulation cotton is placed on the cover plate, and no thermal insulation cotton is placed on the window for placing the sample; the thermal insulation cotton material is aluminum silicate fiber felt, and the thickness is 10mm.
[0062] Hardness test standard for the embodiments and comparative examples: GB / T 4340.1-2009 Vickers hardness test for metal materials;
[0063] Toughness test standard: GB / T229-2020 Charpy pendulum impact test method for metal materials.
[0064] Example 1
[0065] The high entropy alloy is composed of 30% iron, 30% chromium, 18% nickel, 18% manganese, 2.2% vanadium and 1.8% aluminum in atomic ratio;
[0066] The preparation method of the high entropy alloy comprises the following steps:
[0067] (1) Select pure iron, pure chromium, electrolytic nickel and electrolytic manganese with a purity of more than 99.9%, an iron-vanadium alloy with a vanadium content of 80%, and pure aluminum with a purity of 99.99%. The total weight of the ingredients is 40 kg. The raw materials are placed in the order of pure iron, iron-vanadium alloy, pure aluminum, electrolytic manganese, pure chromium and electrolytic nickel into a medium frequency induction heating furnace and vacuumized to 2.0×10 -3Pa, heated to 1550℃ for 2h, and after standing for 5min, the molten alloy was cast into a cast iron mold to obtain a cylindrical ingot with a diameter of 100mm and a length of 650mm;
[0068] (2) free forging the cylindrical ingot obtained in step (1) into a long strip with a size of 40×40×3189 mm, and air cooling to obtain a wrought alloy; wherein the start forging temperature is 1150° C., the heating rate to the start forging temperature is 2° C. / min, the final forging temperature is 1050° C., and the forging ratio is 4.90;
[0069] (3) Cutting the wrought alloy obtained in step (2) into blocks of 40×40×40 mm, placing the blocks in a gradient annealing furnace to anneal one side of the wrought alloy, and air cooling the blocks to obtain a high entropy alloy; wherein the annealing temperature is 680° C., the holding time is 6 h, the heating rate to the annealing temperature is 10° C. / min, the core temperature of the high entropy alloy is 350° C., and the thickness of the hardened layer is 2.8 mm.
[0070] The hardness of the high entropy alloy prepared in Example 1 was measured (from the annealed surface to the core). The results are as follows: Figure 2 shown.
[0071] Figure 2 This is the hardness gradient distribution curve of the high entropy alloy prepared in Example 1.
[0072] from Figure 2 It can be seen that the hardness of the high entropy alloy prepared in Example 1 is distributed in a gradient.
[0073] The surface and core of the annealed high entropy alloy prepared in Example 1 were microscopically inspected, and the results were as follows: Figure 3 and 4 As shown, Figure 3 This is the surface microstructure of the high entropy alloy prepared in Example 1. Figure 4 This is the core microstructure diagram of the high entropy alloy prepared in Example 1.
[0074] from Figure 3 It can be seen that the surface microstructure consists of three regions: the BCC+B2 region with white particles, the FCC+L12 region with a network structure, and the hard phase with dispersed block distribution.
[0075] from Figure 4It can be seen that the core microstructure has only two areas, the BCC+B2 area with white particles and the gray FCC area; the FCC area of the core has no precipitation phase and is a soft phase, so the core alloy has low overall hardness and good toughness; after high-temperature annealing on the surface, an L12 ordered structure is precipitated in the FCC soft phase area, and the hardness of the structure is high, so the FCC soft phase area is transformed into the FCC+L12 hard phase area; in addition, a hard phase with dispersed block distribution is precipitated. The transformation of the microstructure is the reason for the increase in surface hardness.
[0076] Comparative Example
[0077] On the basis of Example 1, the annealing method is changed, that is, the wrought alloy is subjected to overall annealing at 900° C. for 4 h, and then air-cooled to obtain a high entropy alloy.
[0078] The hardness of the high entropy alloy at different annealing and holding temperatures in the comparative example was measured. The results are as follows: Figure 5 shown.
[0079] from Figure 5 It can be seen that the annealing temperature has a significant effect on the hardness of the forged alloy. When the annealing temperature is 650-700℃, the hardness can be increased from about HV320 before annealing to about HV750 after annealing; when the annealing temperature is lower than 400℃, annealing has little effect on the hardness.
[0080] Example 2
[0081] The high entropy alloy is composed of 28% iron, 28% chromium, 20% nickel, 20% manganese, 1.8% vanadium and 2.2% aluminum in atomic ratio;
[0082] The preparation method of the high entropy alloy comprises the following steps:
[0083] (1) Select pure iron, pure chromium, electrolytic nickel and electrolytic manganese with a purity of more than 99.9%, an iron-vanadium alloy with a vanadium content of 80%, and pure aluminum with a purity of 99.99%. The total weight of the ingredients is 40 kg. The raw materials are placed in the order of pure iron, iron-vanadium alloy, pure aluminum, electrolytic manganese, pure chromium and electrolytic nickel into a medium frequency induction heating furnace and vacuumized to 2.0×10 -3 Pa, heated to 1520℃ for 2h, and after standing for 5min, the molten alloy was cast into a cast iron mold to obtain a cylindrical ingot with a diameter of 100mm and a length of 650mm;
[0084] (2) free forging the cylindrical ingot obtained in step (1) into a long strip with a size of 40×40×3189 mm, and air cooling to obtain a wrought alloy; wherein the start forging temperature is 1150° C., the heating rate to the start forging temperature is 3° C. / min, the final forging temperature is 1050° C., and the forging ratio is 4.90;
[0085] (3) Cutting the wrought alloy obtained in step (2) into blocks of 40×40×40 mm, placing the blocks in a gradient annealing furnace to anneal one side of the wrought alloy, and air cooling the blocks to obtain a high entropy alloy; wherein the annealing temperature is 700° C., the holding time is 4 h, the heating rate to the annealing temperature is 15° C. / min, the core temperature of the high entropy alloy is 380° C., and the thickness of the hardened layer is 2.2 mm.
[0086] The hardness of the high entropy alloy prepared in Example 2 was measured (from the annealed surface to the core). The results are as follows: Figure 6 shown.
[0087] Figure 6 This is the hardness gradient distribution curve of the high entropy alloy prepared in Example 2.
[0088] from Figure 6 It can be seen that the hardness of the high entropy alloy prepared in Example 2 is distributed in a gradient.
[0089] The surface and core of the annealed high entropy alloy prepared in Example 2 were microscopically inspected, and the results were as follows: Figure 7 and 8 As shown, Figure 7 This is the surface microstructure of the high entropy alloy prepared in Example 2. Figure 8 This is the core microstructure diagram of the high entropy alloy prepared in Example 2.
[0090] from Figure 7 It can be seen that the surface microstructure consists of three regions: the BCC+B2 region with white particles, the FCC+L12 region with a network structure, and the hard phase with dispersed block distribution.
[0091] from Figure 8 It can be seen that there are only two areas in the core microstructure, the BCC+B2 area with white particles and the gray FCC area. The FCC area in the core has no precipitated phase and is a soft phase, so the core alloy has low overall hardness and good toughness; after high-temperature annealing on the surface, an L12 ordered structure is precipitated in the FCC soft phase area, and the hardness of the structure is high, so the FCC soft phase area is transformed into the FCC+L12 hard phase area; in addition, a hard phase with dispersed block distribution is precipitated. The transformation of the microstructure is the reason for the increase in surface hardness.
[0092] Example 3
[0093] The high entropy alloy is composed of 30% iron, 28% chromium, 19.2% nickel, 18% manganese, 3.8% vanadium and 1.0% aluminum in atomic ratio;
[0094] The preparation method of the high entropy alloy comprises the following steps:
[0095] (1) Select pure iron, pure chromium, electrolytic nickel and electrolytic manganese with a purity of more than 99.9%, an iron-vanadium alloy with a vanadium content of 80%, and pure aluminum with a purity of 99.99%. The total weight of the ingredients is 40 kg. The raw materials are placed in the order of pure iron, iron-vanadium alloy, pure aluminum, electrolytic manganese, pure chromium and electrolytic nickel into a medium frequency induction heating furnace and vacuumized to 2.0×10 -3 Pa, heated to 1600℃ for 1h, and after standing for 5min, the molten alloy was cast into a cast iron mold to obtain a cylindrical ingot with a diameter of 100mm and a length of 650mm;
[0096] (2) free forging the cylindrical ingot obtained in step (1) into a strip with a size of 40×40×3189 mm, and air cooling to obtain a wrought alloy; wherein the start forging temperature is 1150° C., the heating rate to the start forging temperature is 1° C. / min, the final forging temperature is 1050° C., and the forging ratio is 4.90;
[0097] (3) Cutting the wrought alloy obtained in step (2) into blocks of 40×40×40 mm, placing the blocks in a gradient annealing furnace to anneal one side of the wrought alloy, and air cooling the blocks to obtain a high entropy alloy; wherein the annealing temperature is 650° C., the holding time is 10 h, the heating rate to the annealing temperature is 5° C. / min, the core temperature of the high entropy alloy is 310° C., and the thickness of the hardened layer is 3.1 mm.
[0098] The hardness of the high entropy alloy prepared in Example 3 was measured (from the annealed surface to the core). The results are as follows: Fig. 9 shown.
[0099] Fig. 9 This is the hardness gradient distribution curve of the high entropy alloy prepared in Example 3.
[0100] from Fig. 9 It can be seen that the hardness of the high entropy alloy prepared in Example 3 is distributed in a gradient.
[0101] The surface and core of the annealed high entropy alloy prepared in Example 3 were microscopically inspected. The results are as follows: Fig.10 and 11 As shown, Fig.10This is the surface microstructure of the high entropy alloy prepared in Example 3. Fig.11 This is the core microstructure diagram of the high entropy alloy prepared in Example 3.
[0102] from Fig.10 It can be seen that the surface microstructure consists of three regions: the BCC+B2 region with white particles, the FCC+L12 region with a network structure, and the hard phase with dispersed block distribution.
[0103] from Fig.11 It can be seen that the core microstructure also has three regions, the BCC+B2 region with white particles, the gray FCC region, and the hard phase with dispersed block distribution. The FCC region of the core has no precipitated phase and is a soft phase, so the core alloy has low overall hardness and good toughness; due to the high vanadium content of the alloy, there is also a hard phase in the core of the forged alloy, which is a vanadium-chromium-rich hard phase. After high-temperature annealing on the surface, an L12 ordered structure precipitated in the FCC soft phase region, and the hardness of the structure was high, so the FCC soft phase region was transformed into the FCC+L12 hard phase region. The transformation of the microstructure is the reason for the increase in surface hardness.
[0104] The composition and structural properties of the high entropy alloys prepared in Examples 1 to 3 are shown in Table 1.
[0105] Table 1 Composition and structural properties of high entropy alloys prepared in Examples 1 to 3
[0106]
[0107] It can be seen from Table 1 that the surface hardness of the high entropy alloy provided by the present invention reaches above HV740, the depth of the hardened layer is 2-4 mm, and the impact toughness of the core is greater than 60 J / cm 2 .
[0108] It can be seen from the above embodiments that the hardness of the high entropy alloy prepared by the preparation method provided by the present invention is gradient distributed, and has the characteristics of "hard outside and tough inside".
[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high entropy alloy, comprising the following steps: (1) melting, casting and forging the alloy raw materials in sequence to obtain a wrought alloy; (2) Annealing one side of the wrought alloy obtained in step (1) to obtain a high entropy alloy.
2. The preparation method according to claim 1, characterized in that The smelting temperature in step (1) is 1500-1600° C., and the smelting time is 0.5-2 h.
3. The preparation method according to claim 1, characterized in that In the step (1), the starting forging temperature is 1150-1200° C., and the forging ratio is 4-5.
4. The preparation method according to claim 3, characterized in that The rate of heating to the start forging temperature is 1-3°C / min.
5. The preparation method according to claim 1, characterized in that The thickness of the wrought alloy in step (2) is ≥10 mm.
6. The preparation method according to claim 1, characterized in that The holding temperature of the annealing treatment in step (2) is 650-700° C., and the holding time of the annealing treatment is 4-10 hours.
7. The preparation method according to claim 1, characterized in that During the annealing treatment in step (2), the core temperature of the wrought alloy is below 400°C.
8. The preparation method according to claim 1, characterized in that The thickness of the hardened layer of the high entropy alloy in step (2) is 2 to 4 mm.
9. A high entropy alloy prepared by the preparation method according to any one of claims 1 to 8.
10. The high entropy alloy according to claim 9, characterized in that Calculated by atomic ratio, the composition includes: 28-30% iron, 28-30% chromium, 18-20% nickel, 18-20% manganese, 1.8-3.8% vanadium and 1.0-2.2% aluminum.
